Role of EBNA-1 in arresting replication forks at the Epstein-Barr virus oriP family of tandem repeats. - Dhar, V (1991)
The 20-member family of 30-bp tandem repeats located within the oriP region of Epstein-Barr virus (EBV) can act as a transcriptional enhancer in the presence of EBV nuclear antigen 1 (EBNA-1). A replication fork barrier and a termination site of plasmid replication in human B cells is also found within or near the EBV tandem repeats. Within each tandem repeat is a consensus binding sequence for the EBNA-1 protein that is required for extrachromosomal maintenance of oriP-containing plasmids. To investigate the factors that contribute to the arrest of replication forks and termination in the region of the family of repeats, we have used an in vitro replication system in which replication of EBV recombinant plasmids is initiated from the simian virus 40 (SV40) DNA replication origin in the presence of SV40 T antigen and soluble extracts prepared from human cells. The system can support bidirectional replication, initiating from the SV40 DNA origin with termination occurring in a region opposite the origin. Using two-dimensional agarose gel electrophoresis, we observed a barrier to replication forks in the presence of EBNA-1 in the region of the EBV repeats. Termination occurs at or near the tandem repeats in a manner similar to that observed in vivo (T.A. Gahn and C.L. Schildkraut, Cell 58:527-535, 1989). Reducing the number of repeats from 20 to 6 had little effect on the strength of the replication fork barrier. In the absence of EBNA-1, replication forks also arrested at the EBV repeats, but at a much lower efficiency. The addition of competitor DNA containing the EBV family of repeats can almost completely abolish the replication barrier produced in the presence of EBNA-1.